Knowledge of Exclusive Breastfeeding and Associated Factors Among Fathers of Infants Under 1 year in Northeast Ethiopia. - Animaw, Mulugeta; Assefa, Abdulaziz; Belay, Aynalem; Tefera, Zenebe; Workie, Amare; Abera, Mangistu (Inquiry (00469580), 2026)
Exclusive breastfeeding is defined as a condition in which the child takes only breast milk and no additional food, water, or other liquids for the first 6 months of its life. Even though many contributing factors are present for this problem, fathers' knowledge about breastfeeding is a vital and neglected part. A baby has a higher chance of being breastfed if the father has more knowledge regarding exclusive breastfeeding. This study aims to assess knowledge of exclusive breastfeeding and associated factors among fathers of infants aged under 1 year in Northeast Ethiopia, 2023. A community-based cross-sectional study was done with 620 fathers whose wives had given birth in the previous year. A multistage sampling process was used to choose study participants. A pretested and organized questionnaire was used to collect data, which was administered via interviews. The information was entered into EpiData version 4.6 and then exported to SPSS version 25 for analysis. Binary logistic regression was used, and variables having a P -value lower than.05 were regarded as significant factors impacting the outcome variable. In this study, a total of 612 participants were involved. Out of 612, 374(61.1%) of participants had good knowledge (95% CI 57.2-64.9). Forty percent of respondents were in the age group of 30 to 34 years. The majority of the respondents, 420 (68.6%), were urban residents. Living in a rural residence(AOR = 0.16, 95% CI: 0.1-0.33), attending secondary school and above (AOR = 3.83, 95% CI: 1.47-13.04), employers (AOR = 1.87(1.20-5.4)), accompanying during antenatal contact(AOR = 5.15, 95% CI: 2.07-12.81), and wives' postnatal follow-up (AOR = 6.1, 95% CI: 2.90-14.25) were independent predictors of good knowledge level of respondents. Nearly two-thirds of fathers had good knowledge of exclusive breastfeeding. Key predictors included rural residence, wives' postnatal care, accompanying antenatal visits, higher education, and employment status.